Features of subject of the crimes foreseen by Art. 298 of CC of Ukraine - Базелюк, В. В. (Problems of legality, 2013)
In the articles the varieties and features of subject of the illegal conducting of searching works on the object of archaeological legacy, elimination, destruction or damage of objects of cultural legacy are explored.